Response of aboveground organs of Woody plants in the Qaidam Basin in China to aridity via functional economic spectra - Siyu Liu; Yiwen Kong; Yue Fan; Yanhong Liu (BMC Plant Biology)
Abstract Background Plant economic profiles involve trade-offs between many functional traits of a plant that are often used as indicators to characterize major adaptive strategies, thus providing insights into plant distribution, ecosystem processes, and function. However, research on plant economic profiles in extreme habitats is limited, and most studies on economic profiles have focused on single organs, with fewer studies on economic profiles among aboveground (leaf and stem) organs. Methods Taking the desert area of Qaidam Basin as the research object, 8 leaf traits and 8 stem traits of 25 dominant woody plants accounting for more than 80% of biomass in 130 sample plots under different aridity gradients were quantitatively analyzed. The functional strategies and economic profiles of aboveground organs of desert plants adapted to arid environment were studied. Results Traits of leaves and stems represent distinct resource strategies. Leaf traits emphasize resource acquisition, while stem traits highlight conservation. The leaf economic spectrum (LES) and stem economic spectrum (SES) strategies showed an inverse pattern, with leaf traits shifting from opportunistic to conservative strategies and stem traits shifting from conservative to stabilizing strategies as aridity intensified, revealing an integrated aboveground economic spectrum of the plant along the aridity gradient. Moreover, there was a significant negative correlation between leaf and stem function strategies and reflected significant leaf-stem trade-offs. Conclusion The functional traits of plants can reflect plant responses to environmental changes, and the aboveground economics spectrum helps researchers understand the response of plants as a whole to environmental differences, thus deepening the knowledge of the economic spectrum of plants. The patterns of economic profiles embodied by plants in response to aridity were revealed in this study. The trade-off between the LES and SES demonstrated the existence of an aboveground economic spectrum, providing a scientific basis for understanding the survival mode and adaptive variation pattern of desert plants.